HUBUNGAN TOTAL ASSET TURNOVER DAN CURRENT RATIO DENGAN HARGA SAHAM PADA PT HANJAYA MANDALA SAMPOERNA Tbk PERIODE 2013-2022 - Fadhla Ramadhani, Adira; Sairin (Journal of Research and Publication Innovation, 2024)
This study aims to determine the relationship of Total Asset Turnover (TATO), Current Ratio (CR) to Stock price at PT Hanjaya Mandala Sampoerna Tbk for the period 2013-2022. The research method used is Quantitative method. The data analysis used is the classic assumption test, multiple regression analysis, t-test hypothesis testing, f-test and determination coefficient test (R2). The results showed that TATO has a significant value of 0.010 <0.05 and a t value of 3.476> 2.364, this indicates that the TATO variable partially has a significant effect on Stock Price, and the CR value has a significant value of 0.001 <0.05 and a t value of 5.985> 2.364, this indicates that the CR variable partially has a significant effect on Stock Price, and while the TATO and CR variables show that it has a significant value of 0.001 <0.05 and the value of f count 23.427> 4.350, this indicates that the TATO and CR variables simultaneously have a significant effect on Stock Price. The multiple correlation coefficient value is 0.933, which means that there is a very strong relationship between Total Asset Turnover and Current ratio on Stock price. The coefficient of determination (R2) value is 87% while the remaining 13% is influenced by other variables not examined in the study.